Acute kidney infarction: Not so rare renal disease. A single-center experience with endovascular fibrinolytic therapy - Scarpioni R; De Amicis S; Bodini FC; Albertazzi V; Michieletti E (Archives of Clinical Nephrology - Peertechz Publications, 2022)
Renal Infarction (RI), a rare cause of renal damage characterized by the abrupt interruption of flow in the renal artery, is often recognized late or may even remain undiagnosed since symptoms are non-specific and may be confused with other pathologies, such as pyelonephritis or nephrolithiasis. In situ thrombosis and thromboembolism are the main causes, but often the real cause is, gf unrecognized. The disease is often underdiagnosed and the diagnosis of certainty can be established with ultrasonography Doppler of renal arteries or with second-level diagnostic tools (contrast-enhanced computer tomography, magnetic resonance with gadolinium, and renal scintigraphy) or third level tests (renal arteriography). The therapeutic approach depends on the cause of RI, from the time from onset of ischemia, from the presence of kidney function impairment, and may include systemic anticoagulant therapy, renal angioplasty with or without stenting, loco-regional endovascular fibrinolytic therapy or surgery, as the last chance. In literature, there are neither guidelines nor evidence about any treatment superiority. Here we describe a paradigmatic case in a 51-years-old man hospitalized because of sudden flank pain: the clinical picture, the high serum level. Moreover, we report our 7-years' experience with 24 cases of RI, mean age 70 /±15 years, 14/24 men, 16/24 presented with hematuria, frequently associated with the history of CKD (16/24). Fifteen of them (62%) were classified as idiopathic and 9 of them were successfully treated with endovascular fibrinolytic treatment. A review of the literature is also provided.